Unveiling Post Engagement Rate Using Predictive Analytics Model for Instagram Accounts of Coffee Shops in West Jakarta - Sutanto, Sachio Dariell (Journal Integration of Management Studies, 2023)
The rapid growth of the coffee shop industry is currently happening in Indonesia. The rapid growth induces fierce competition between each other, and one of the areas in Indonesia that is affected by the growing number of coffee shops in Indonesia is West Jakarta. When competing, there is a need for a coffee shop to establish a positive relationship with its customers to promote its products. One of the popular methods of establishing relationships with customers is by using Instagram. The social interaction that happens between the coffee shop and its customers is through liking or commenting on Instagram posts. Those interactions on Instagram will then be quantified by the application itself by the count of likes and comments in the posts. Then, using both quantified metrics, with the addition of the count of followers of the accounts, we are intrigued to create predictive analytics for the engagement metrics in Instagram to predict the engagement rate of future posts. In this study, we will focus on analyzing the Instagram engagement metrics, like, comments, and followers, to predict the engagement rate on an Instagram post. With multiple linear regression, we developed a model to forecast the outcome of future Instagram posts. The prediction variables include the factors that we can input when posting on Instagram, such as Captions, Locations, Audio, Hashtags, and the type of the Post itself. Although we have analyzed several variables that we may modify when posting on Instagram, we found out that not all variables exhibit significant impacts on the engagement rate, only two variables have a significant impact on the predicted value of an Instagram post. In consequence, this study serves as a foundation for predicting engagement rates of Instagram posts of coffee shops, helping coffee shop owners on creating a plan for their Instagram posts.